Kajian Mengenai Academic Burnout pada Mahasiswa Fakultas Kedokteran - Della Amelia Juanda; Dewi Rosiana (UNISBA Press, 2024)
Abstract. Academic burnout is a condition of physical, mental, and emotional exhaustion experienced by students due to excessive academic pressure. This term is adapted from the concept of